Qualitative Study of the Declining Trend of Local Retribution in Regency/City in Indonesia - Indrawati, Raden Ajeng; Muslimin, Muslimin (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This qualitative study analyzes public perceptions of the declining trend in local retribution within Indonesian regencies and cities. The research examines factors such as public awareness, trust in local governance, economic challenges, and their impact on compliance behavior. Findings indicate that limited understanding of retribution policies, perceived lack of transparency in fund usage, and economic hardships significantly contribute to reduced compliance. Additionally, skepticism toward local governance and perceived inefficiency further discourage retribution payments. To address these challenges, strategies are suggested to improve transparency, strengthen administrative efficiency, and enhance public services, thereby fostering trust and compliance. Policy adjustments should be made to reflect regional economic conditions and ensure fair retribution systems, supported by public education and technological improvements in payment processes. The study underscores the importance of community involvement in policy-making and tailored approaches to address the specific needs of different regions, ultimately contributing to sustainable local revenue growth and better fiscal management. By improving awareness, transparency, and economic fairness, local governments can encourage higher compliance, improve financial independence, and better support public services.